The state ecological expertise: the concept, the location, the value of SER in the system of expert activity of public authorities to prevent negative impact on the environment - D. M. Mishukov (Путеводитель предпринимателя)
State ecological expertise (SEE) is independant legal institution. Existance of this institution is due to necessity of preliminary state control to prevent potentially dangerous act for environment and to ensure the constitutional right of everyone for favorable environment. SEE is closely related to the procedure of assessment of the impact on the environment, because the result of this procedure is a part of documents which should be presented for SEE. But SEE is not the only expertise to check compliance of the project documents with the environmental requirements. Sometimes the object of SEE coincides with object of State expertise of project documentation аnd in this situation we have duplication of state functions.